Reimagining Dussehra through AI-Generated Anime: Examining Global Perceptions of Indian Culture - KUMAR, Uday G.; SAILESH, Bhaskar (Journal of Environmental Management and Tourism; Vol 16 No 4 (2025): JEMT, Volume XVI, Issue 4(80), Winter 2025DO - 10.14505/jemt.v16.4(80).08, 2025)
To examine how generative AI reimagines Dussehra through anime-style visuals and to assess how these representations influence global perceptions of Indian culture. The study uses a qualitative analysis of secondary data from AI-art platforms, digital archives, and audience discussions. It interprets visual patterns, circulation dynamics, and viewer responses through the proposed AI–Culture–Perception Framework. AI-generated anime increases the global visibility of Dussehra by translating mythic symbols into accessible visual forms. However, the outputs may simplify cultural nuances or introduce aesthetic distortions due to algorithmic bias and stylistic blending. Audience reactions show a mix of appreciation, curiosity, and concern about authenticity. The study offers one of the first analyses of festival representation through AI-generated anime and introduces a conceptual model explaining how cultural meaning is reshaped through AI mediation and platform circulation. The research relies solely on secondary data; future studies should include empirical audience surveys for deeper insight.